High performance epoxy resin composites modified with multifunctional thiophene/phosphaphenanthrene-based flame retardant: Excellent flame retardance, strong mechanical property and high transparency. (15th December 2021) - Wang, Hao; Yuan, Jun; Zhu, Zongmin; Yin, Xianze; Weng, Yunxuan; Wang, Zhaojia; Yang, Feihua; Zhan, Jiayu; Wang, Hua; Wang, Luoxin
Abstract: It is always a challenge to prepare multifunctional epoxy resins (EP) composites with excellent flame retardance, mechanical property and high transparency. In this work, a reactive flame-retardant (BDO) was synthesized from DOPO, 3, 5-diamino-triazolz and thiophene-2-formaldehyde, and taken to prepare EP/BDO composites. Surprisingly, benefitting from the synergy of efficient flame retardant unit (DOPO structure), catalytic curing unit (triazole structure) and optical functional structure (thiophene-2-formaldehyde), the EP composites with excellent comprehensive performance was obtained. In detailed, after adding only 5 wt% BDO, the EP composites passed the UL-94 V-0 level, and the limiting oxygen index was increased to 33% from 22.5% of neat EP. At the same time, EP/BDO-5 showed obvious heat suppression and smoke suppression effects. Besides, EP/BDO-5 presented excellent mechanical strength, that the tensile strength and bending strength were increased by 25% and 30% compared with neat EP. Moreover, EP/BDO composites maintained the same good light transmittance as neat EP, and also presented enhanced Tg and dielectric property. In addition, the dual phase flame-retardant mechanism was revealed through systematically analyzing residues after combustion and the gaseous phase products of flame retardant. The above results indicated EP/BDO composites with excellent comprehensive performance possessed a great potential application in high-performance composites fields.